Egypt’s water budget deficit and suggested mitigation policies for the Grand Ethiopian Renaissance Dam filling scenarios - Essam Heggy; Zane Sharkawy; Abotalib Z Abotalib (Environmental Research Letters, 2021)
The Nile River is a unique environmental system and essential water resource for its basin riparian nations. Population growth, changes in precipitation patterns, damming and usage rights disputes present extreme challenges in utilizing and managing the basin’s primary water resource. These stress factors are of particular concern for highly populated Egypt, the furthest downstream recipient of the Nile’s water flow. Previously, colonial agreements had granted Egypt and Sudan the majority of water use rights on the Nile without neighboring Ethiopia receiving any specific allocation. Today, Ethiopia plans to increase its energy production through its Nile-powered Grand Ethiopian Renaissance Dam (GERD). While the 74-billion cubic meter (BCM) dam presents promising development opportunities for Ethiopia, the Nile’s altered flow will increase the existing water deficit for Egypt—the quantification and mitigation of which are still largely unconstrained and under intense debate. To address this deficiency, we estimate that the median total annual water budget deficit for Egypt during the filling period, considering seepage into the fractured rocks below and around the GERD reservoir, as well as the intrinsic water deficit and assuming no possible mitigation efforts by Egyptian authorities, will be ∼31 BCM yr ^−1 , which would surpass one third of Egypt’s current total water budget. Additionally, we provide a feasibility index for the different proposed solutions to mitigate the above deficit and assess their economic impact on the GDP per capita. Our results suggest that the unmet annual deficit during the filling period can be partially addressed by adjusting the Aswan High Dam (AHD) operation, expanding groundwater extraction and by adopting new policies for cultivation of crops. If no prompt mitigation is performed, the short-term three-year filling scenario would generate a deficit that is equivalent to losses to the present cultivated area by up to 72% resulting in a total loss of the agricultural GDP by $51 billion during the above-mentioned filling period. Such figures are equivalent to a decrease in the total national GDP per capita by ∼8%, augmenting existing unemployment rates by 11%, potentially leading to severe socioeconomic instability.